The relationship between audit committees, internal controls and audit evidence : Tanzania’s experience / Mwamba Ally Jingu - Jingu, Mwamba Ally (2015)
This study investigates two research questions arising from the recommendation of the Tanzania Guideline on Corporate Governance (TGCG) 2002, and the International Standards on Audit Evidence issued (ISAs). The first question aims at understanding whether the characteristics of audit committee effectiveness: independence, size, financial expertise and frequency of meetings in a year are related to the quality of internal control. The second question aims at understanding whether the entities’ internal control effectiveness is related to the persuasiveness of audit evidence. This study is conducted in a Tanzanian context and focuses on the perspectives of external auditors. A total of 200 external auditors working as partners, managers or audit seniors from the Big Four audit firms and large local audit firms in Tanzania participated in this survey. The study finds that audit committee effectiveness measured by the majority of independent members in the audit committee, with the presence of one accounting financial expert, and holding at least four meetings in a year is related to high quality of an entity’s internal controls. Specifically, the results indicate that auditors’ opinion on the reliability of an entity’s internal control will be more favourable if an entity’s audit committee has a majority of independent members, has at least one accounting financial expert, and holds at least four meetings in a year. However, the association between the majority of independent members in the audit committee and internal control effectiveness is only favourable where the chairperson of the audit committee is also independent. The effect of having a non-independent chairperson in an audit committee is that auditors will assess the entity’s internal controls as less favourable even if the audit committee has a majority of independent members. Similarly, the effect of not having a majority independent member in an audit committee is that auditors will assess the entity’s internal controls as less favourable even if the audit committee has an independent chairperson. The findings on the independence of the chairpersons help to reconcile the mixed findings of prior research that examined the relationship between the proportion of independent members in the audit committee and the dimensions of audit committee effectiveness. The study also finds that there is a relationship between internal control effectiveness and the persuasiveness of both external and internal audit evidence items and that strong internal control are related to increases in persuasiveness of audit evidence. However, the relationship indicates that internal control effectiveness increases the persuasiveness of internal evidence items by a larger margin compared to the external evidence items. Furthermore, results show that auditors consider the persuasiveness of internal evidence items generated under an entity’s strong internal control system to be the same as evidence items obtained from independent sources outside the entity.